EVALUASI TINGKAT KERASIONALAN PENGGUNAAN ANTIBIOTIK PROFILAKSIS DAN TIMBULNYA INFEKSI LUKA OPERASI PADA OPERASI SECTIO CAESAREA TANPA KOMPLIKASI DI RSIA MELANIA BOGOR - , osie listina,S.Farm.Apt ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to evaluate the use of antibiotic prophylaxis in prevention of surgical wound infections, antibiotic prophylaxis usage patterns suitability and assess the factors that led to the emergence of surgical wound infection.Observational research method used by analytical study through a retrospective data retrieval of medical records of patients who underwent surgery in RSIA Melania sectio caesarea Bogor period from January to Juny 2010. The number of patients who experienced events of surgical wound infection (ILO) and who did not experience the incidence of surgical wound infection (Non ILO) each were 58 patients. Patients who have comorbidities experienced postoperative wound infection incidence of 3.45% and did not undergo surgical wound infection of 2.59%. While patients who do not have comorbidities experienced postoperative wound infection incidence of 46.55% and did not undergo surgical wound infection at 47.41%. Patients who underwent elective surgery experienced event type of surgical wound infections by 13.80% and did not undergo surgery wound infection incidence of 41.38%. While patients who underwent surgery type cito experienced postoperative wound infection incidence of 36.20% and did not undergo surgical wound infection incidence of 8.62%. Patients who underwent surgery first round has the incidence of surgical wound infection at 16.38% and did not undergo surgical wound infection incidence of 38.80%. While patients who underwent surgery Â³ second round experience of surgical wound infection incidence of 33.62% and did not undergo surgical wound infection at 11.20%. Based statistical analysis found no relationship between the incidence of accompanying diseases with surgical wound infections, but there is a relationship between type of surgery and rounds of surgery on the incidence of surgical wound infections. Compliance is the use of prophylactic antibiotics is in conformity with the standards include dose, route, duration and time of administration. The case of occurrence of potential drug interactions occur by 21.55% of 116 patients observed, this illustrates the need for vigilance so that therapy can be lowered incidence of drug interactions.